Effect of two teaching methods on nursing students' acquisition of patient-centered communication competence in older people care: a cluster randomized trial - Cortés-Rodríguez, Alda Elena; López-Rodríguez, María Mar; Roman, Pablo; Granero-Molina, José; Fernández-Sola, Cayetano; Hernández-Padilla, José Manuel (Frontiers in Public Health, 2024)
IntroductionPatient-centered communication is an essential skill in nursing, particularly in the care of older adult patients. However, generation Z nursing students, who primarily communicate through digital platforms, face unique challenges in adapting to traditional face-to-face communication with older adults. As a result, there is a need for teaching methods that align with this generation's learning style to enhance their communication skills. This study aimed to compare the effectiveness of two teaching methods—standardized patient simulation and role-play—on nursing students' acquisition of patient-centered communication competence in older people care.MethodsA controlled cluster-randomized trial was conducted with 124 nursing students, divided into eight teaching groups. Students participated in either a standardized patient simulation or a role-play workshop, each consisting of a 1.5-h online module and a 1.5-h face-to-face session. The three components of patient-centered communication competence—knowledge, skills, and self-efficacy—were assessed using simulated scenarios at pre-test, post-test, and 6-week follow-up. Between-group and within-group differences were measured based on the number of students who achieved competence.ResultsBoth interventions significantly improved students' knowledge, skills, and self-efficacy in patient-centered communication between pre- and post-tests, with improvements maintained at follow-up. No significant differences were found between the two methods.ConclusionsBoth standardized patient simulation and role-play are effective in enhancing patient-centered communication competence in older people care. However, neither method was found to be superior in teaching knowledge, skills, or self-efficacy.